2016
DOI: 10.1002/jcaf.22144
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Driven Activity‐Based Costing: An Implementation in a Manufacturing Company

Abstract: This article demonstrates the implementation of time‐driven activity‐based costing (TDABC) in a manufacturing company, showing how it can provide far more relevant information about product profitability and capacity utilization than standard costing. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…In Equation (1), n ∑ i=1 (t oi +t ci )k o BA i represents the total rework mix processing costs, and the associated constraints are shown in Equation (17). t oi is the time of rework mix processing and t ci is the time to shift each batch of product i to the rework mix department [57][58][59]. After mixing, the rubber charge is dropped into a chute and fed by an extruding screw into a roller die.…”
Section: Total Rework Costmentioning
confidence: 99%
“…In Equation (1), n ∑ i=1 (t oi +t ci )k o BA i represents the total rework mix processing costs, and the associated constraints are shown in Equation (17). t oi is the time of rework mix processing and t ci is the time to shift each batch of product i to the rework mix department [57][58][59]. After mixing, the rubber charge is dropped into a chute and fed by an extruding screw into a roller die.…”
Section: Total Rework Costmentioning
confidence: 99%
“…To the best of our knowledge, only the study by Öker and Adigüzel (2010) deals with the production process of a manufacturing company. The authors concluded that the two types of resources (human labour work and machine work) used in such companies make it necessary to calculate two different practical capacities, thus entailing additional work.…”
Section: Research Focus: Is Tdabc Right For All Companies?mentioning
confidence: 99%
“…In fact, the studies on TDABC in service companies show that for this type of company, it is only necessary to resort to human labour resources to express the 8 practical capacities of companies (e.g., Demeere et al, 2009;Dalci et al, 2010;Giannetti et al, 2011;Somapa et al, 2012;Everaert et al, 2012;Kaplan et al, 2014;Basuki and Riediansyaf, 2014;Campanale et al, 2014). As a result, Öker and Adigüzel (2010) believe TDABC is a more appropriate costing system for service companies than for manufacturing. Furthermore, Souza et al (2010) concluded that the unstable and unpredictable production environment in make-to-order companies complicates the definition of time equations, and TDABC is therefore unsuitable.…”
Section: Research Focus: Is Tdabc Right For All Companies?mentioning
confidence: 99%
See 1 more Smart Citation
“…While a multitude of applications for existing costing concepts have been continuously broadened (e.g., time-driven activity-based costing [4], [5], [6], [7]), at the same time, their degree of specialization has increased (e.g., dedicated methodologies for woodworking [8] or welding [9]). As a result of such methodological diversity, recent research even addresses the selection of appropriate concepts within specific contexts [10].…”
Section: Introductionmentioning
confidence: 99%